2013
DOI: 10.1097/mca.0b013e328362b2c8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D insufficiency on the epicardial coronary flow velocity and endothelial function

Abstract: A strong association was found between VD insufficiency and the SCF phenomenon. In addition, VD insufficiency was associated with endothelial dysfunction and subclinical atherosclerosis. We believe that further studies are required to clarify the role of VD in patients with SCF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Vitamin D insufficiency has been associated with higher endothelial activation and dysfunction [17]. According to some authors, vitamin D inadequacy in an adult, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D insufficiency has been associated with higher endothelial activation and dysfunction [17]. According to some authors, vitamin D inadequacy in an adult, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, it has been proposed that vitamin D deficiency and/or insufficiency is associated with impaired endothelial function [6]. Furthermore, several studies have shown an inverse correlation between serum 25-hydroxyvitamin D (25(OH)D) levels and biomarkers of endothelial dysfunction in patients with hypertension, T2DM, coronary artery disease and stroke [1517]. Vitamin D insufficiency is more prevalent in obese individuals [1820].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D level lower than 30 ng/mL has also been associated with reduced velocity of coronary blood flow, endothelial dysfunction, and subclinical atherosclerosis [20]. Vitamin D level lower than 20 ng/mL was detected in obese children with increased oxidative/nitrosative stress, markers of inflammation, and endothelial activation [21].…”
Section: Resultsmentioning
confidence: 99%
“…The response of the vessel diameter to reactive hyperemia was expressed as percentage change relative to the diameter immediately before cuff inflation. FMD was expressed as the percentage change from baseline in the brachial artery internal diameter following reactive hyperemia [18, 19]. The interobserver variability of the FMD measurement was 3.5% in our study.…”
Section: Methodsmentioning
confidence: 93%